DEVELOPMENT AND IMPLEMENTATION OF THE MOTHER AND CHILD SHUTTLE SYSTEM FOR WAREHOUSE MANAGEMENT AND OPERATION - Huynh, Anh-Tuan; Le, Quoc-Tuan; Lam, Xuan-Minh-Nhat; Nguyen, Thi-Ngoc-Thao; Le, Thi-Hong-Lam; Truong, Nhat-Bang; Vu, Bao-Huy; Nguyen, Kieu-Vinh; Tran, Huu-Nhan; Nguyen, Phong-Luu; Nguyen, Binh-Hau; Nguyen, Thanh-Binh; Nguyen, Van-Hiep; Nguyen, Ngoc-Hung (Indonesian Journal of Engineering and Science, 2026)
The increasing complexity of warehouse operations and the rapid growth of e-commerce demand advanced Automated Storage and Retrieval Systems (AS/RS) that are efficient, flexible, and reliable. This study presents the design and implementation of a Mother and Child Shuttle System integrated with a hybrid communication architecture and an intelligent control interface. The system is developed based on kinematic and dynamic analysis to optimize shuttle motion using an acceleration–constant velocity–deceleration profile, ensuring stable operation and accurate positioning. A block-based control architecture incorporating PLC, sensors, motor drivers, and wireless communication enables coordinated system operation. The hardware prototype, including the Mother Shuttle, Child Shuttle, and storage rack, is successfully constructed and validated under real conditions, demonstrating stable performance and effective component integration. In addition, a user-friendly interface is developed to support real-time monitoring, control, and alarm management, enhancing system reliability and operational safety. The proposed system provides a practical solution for improving efficiency and scalability in modern warehouse automation.